2019
DOI: 10.1111/1750-3841.14812
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐Casein and Beta‐Lactoglobulin from Cow Milk Exhibit Antioxidant Activity: A Plausible Link to Antiaging Effects

Abstract: Studies on the discovery and function of antioxidants are consistently being performed because oxidative stress can cause various diseases. Many compounds and natural products have antioxidant activity in vitro; however, it is often difficult to reproduce their effects in vivo. Additionally, methods to measure antioxidant activities in cells are also scarce. Here, we investigated the antioxidant activity of milk proteins by observing the formation of arsenite‐induced stress granules as a tool to evaluate antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…110 In contrast, BLG depletion reduces the antioxidant activities of milk by 50%, whereas purified BLG is considered only a mild antioxidant. 111 Studies have also shown that the ability of BLG to bind to ligands such as retinol and palmitic acid is lost following heating, 112 just as the antioxidant activity in milk is reduced after heating, 111,113 while its antigenicity is increased at the same time. 26,112 Collectively, we have discovered a previously unrecognized role of the major milk protein BLG to transport ligands to immune cells, thereby providing an immune-regulatory effect resulting in resilience to immune activation and protection against allergic sensitization and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…110 In contrast, BLG depletion reduces the antioxidant activities of milk by 50%, whereas purified BLG is considered only a mild antioxidant. 111 Studies have also shown that the ability of BLG to bind to ligands such as retinol and palmitic acid is lost following heating, 112 just as the antioxidant activity in milk is reduced after heating, 111,113 while its antigenicity is increased at the same time. 26,112 Collectively, we have discovered a previously unrecognized role of the major milk protein BLG to transport ligands to immune cells, thereby providing an immune-regulatory effect resulting in resilience to immune activation and protection against allergic sensitization and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Major protein fractions present in human and bovine milk (casein and whey) and some milk protein-derived peptides have been reported to have antioxidant activity [2][3][4][5][6][7]. In particular, specific casein hydrolysates from bovine milk demonstrate antioxidant activity via radical scavenging properties in both aqueous and lipid model systems [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…They can serve various physiological functions such as energy production, phagocytosis, cell growth, and intracellular signaling. Normally, free radical is maintained in the moderate concentration by their own defense mechanism including antioxidative enzymes such as superoxide dismutase, catalase, and glutathione peroxidase and small molecule glutathione [1]. However, the concentration and/or activity of endogenous antioxidants will reduce with aging and cause overproduction of free radicals and the occurrence of oxidative stress, which will further result in cellular injury by damaging DNA, lipids, and protein [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Herbs have played a major role in traditional medicines for over a thousand years in China, which have a variety of health-benefit effects including antioxidant, anti-inflammatory, neuroprotective, and anticarcinogenic activities [1]. Many studies have demonstrated that the antioxidant activity of herbs is attributed to the bioactive composition such as flavonoids, alkaloids, and polyphenols [8,9].…”
Section: Introductionmentioning
confidence: 99%